THE AUDIT REPORT. - McGladrey, I. B. (The Accounting Review, 1951)
Abstract In this article the author stimulates interest in a co-operative effort through the facilities of the American Institute of Accountants, of the American Accounting Association, to improve the manner of audit reporting. According to the author these organizations have had a profound influence in developing accounting and auditing standards and techniques. The author considers the questions such as how best to indicate clearly the auditor's responsibility, what information should be included in the report, and how should the information be presented? He states that the auditor should prepare his report so that no one need be deceived in any case. In any discussion of the accountant's responsibility it should not be assumed that the client has no responsibility for the representations in his own financial statements which have been audited by a certified public accountant. In order to clarify his responsibility the accountant may give a disclaimer of an opinion. This means that the scope of his work was not sufficient for him to express an over-all opinion on the financial statements taken as a whole, or that some other circumstance prevented the expression of such an opinion.